EFEKTIVITAS PELAYANAN PERPUSTAKAAN KELILING DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KUBU RAYA - Asrifah, Ade Angga; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to determine the extent of the effectiveness of mobile library services in Sui Raya District, Kubu Raya Regency. The aim of the researchers from this study was to find out how effective the users of mobile library services and the constraints in mobile library services in the District of Kubu Raya.Researchers used qualitative methods. Data collection techniques conducted by researchers. Using observation x and documentation when the research was conducted. Data analysis techniques used by researchers in this study using qualitative data analysis that produces descriptive data in the form of words or verbal from a person or it can also be with events that can be observed directly.The results of the study of mobile library services are considered to be quite effective. Effectiveness of mobile library services in Kubu Raya District which covers tasks or functions, plans or programs, rules and regulations and constraints or obstacles that are carried out in mobile library services in Sungai Raya District, Kubu Raya Regency. In Sungai Raya sub-district, Kubu Raya district has the opportunity to use this mobile library service, especially for schools that are still lacking in reading material needed by students and gain insight. However, this mobile library in carrying out its duties is not always as expected. There are several obstacles in the effectiveness of mobile library services in Sungai Raya District, Kubu Raya Regency. These obstacles include facilities and infrastructure and the quality of human resources, time and place of serviceKeywords: Effectiveness, Service, Mobile Library.